2019
DOI: 10.1007/s00167-019-05451-0
|View full text |Cite
|
Sign up to set email alerts
|

It is possible to release the plantaris tendon under ultrasound guidance: a technical description of ultrasound guided plantaris tendon release (UPTR) in the treatment of non-insertional Achilles tendinopathy

Abstract: Purpose Open plantaris tendon excision and ventral paratendinous stripping is a recognised treatment option in selected patients with non-insertional Achilles tendinopathy. The aim of this study was to develop a minimally invasive outpatient technique of ultrasound guided plantaris tendon release (UPTR). Methods A 19 gauge needle, 15 gauge scalpel blade, hook knife (Smith and Nephew, Boston, MA, USA) and a beaver blade (Arthrex, Naples, FL, USA), were used under ultrasound guidance to identify and divide the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As exercise approaches so far have not been successful for the treatment of patients with diagnosed plantaris tendon involvement, it seems that surgical intervention is needed to allow for a return to pain-free Achilles tendon loading in this sub-group. As such, recent studies have begun to explore better diagnostic strategies and use less invasive ultrasound-guided percutaneous surgical treatments [ 19 , 35 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…As exercise approaches so far have not been successful for the treatment of patients with diagnosed plantaris tendon involvement, it seems that surgical intervention is needed to allow for a return to pain-free Achilles tendon loading in this sub-group. As such, recent studies have begun to explore better diagnostic strategies and use less invasive ultrasound-guided percutaneous surgical treatments [ 19 , 35 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment for AT varies widely, and there is no consensus regarding the optimal treatment for both IAT and NIAT. 8 , 9 , 10 , 11 , 12 Extracorporeal shock wave therapy (ESWT) is a widely accepted and effective treatment option for AT. 13 , 14 , 15 A previous study reported that the theories of the effects produced by ESWT could essentially be divided into pain relief, tissue regeneration, and destruction of calcifications.…”
Section: Introductionmentioning
confidence: 99%